Reliability of Symbolic Analysis of Heart Rate Variability and Its Changes During Sympathetic Stimulation in Elite Modern Pentathlon Athletes: A Pilot Study - Gąsior, Jakub S.; Rosoł, Maciej; Młyńczak, Marcel; Flatt, Andrew A.; Hoffmann, Bartosz; Baranowski, Rafał; Werner, Bożena (Frontiers in Physiology, 2022)
Background and purpose: Most studies on heart rate variability (HRV) in professional athletes concerned linear, time- and frequency-domain indices and there is lack of studies on nonlinear parameters in this group. The study aimed to determine the inter-day reliability, and group-related and individual changes of short-term symbolic dynamics (SymDyn) measures during sympathetic nervous system activity (SNSa) stimulation among elite modern pentathletes. Methods: Short-term electrocardiographic recordings were performed in stable measurement conditions with a 7-days interval between tests. SNSa stimulation via isometric handgrip strength test was conducted on the second day of study. The occurrence rate of patterns without variations (0V), with one variation (1V), two like (2LV) and two unlike variations (2UV) obtained using three approaches (the Max-min, the σ and the Equal-probability methods) were analyzed. Relative and absolute reliability were evaluated. Results: All SymDyn indices obtained using the Max-min method, 0V and 2UV obtained using the σ method, 2UV obtained using the Equal-probability method presented acceptable inter-day reliability (the intraclass correlation coefficient between 0.91 and 0.99, Cohen’s d between -0.08 and 0.10, the within-subject coefficient of variation between 4% and 22%). 2LV, 2UV and 0V obtained using the Max-min and σ methods significantly decreased and increased, respectively, during SNSa stimulation – such changes were noted for all athletes. There was no significant association between differences in SymDyn parameters and respiratory rate in stable conditions and while comparing stable conditions and SNSa stimulation. Conclusion: SymDyn indices may be used as reliable non-respiratory-associated parameters in laboratory settings to detect ANS activity modulations in elite endurance athletes. These findings provide a potential solution for addressing the confounding influence of respiration frequency on HRV-derived inferences of cardiac-autonomic function. For this reason, SymDyn may prove to be preferable for field-based monitoring where measurements are unsupervised.